2017
DOI: 10.1038/cr.2017.113
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of MAPK11 or HIPK3 reduces mutant Huntingtin levels in Huntington's disease models

Abstract: Most neurodegenerative disorders are associated with accumulation of disease-relevant proteins. Among them, Huntington disease (HD) is of particular interest because of its monogenetic nature. HD is mainly caused by cytotoxicity of the defective protein encoded by the mutant Huntingtin gene (HTT). Thus, lowering mutant HTT protein (mHTT) levels would be a promising treatment strategy for HD. Here we report two kinases HIPK3 and MAPK11 as positive modulators of mHTT levels both in cells and in vivo. Both kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 88 publications
1
28
0
Order By: Relevance
“…HIPK2 activity positively correlates with neurodegeneration in ALS (12). Loss of function of HIPK2 has been linked to the development of Alzheimer's disease (13), whereas loss of HIPK3 was implicated as beneficial in Huntington's disease (14).…”
Section: The Homeodomain-interacting Protein Kinase (Hipk) Family Is mentioning
confidence: 99%
See 1 more Smart Citation
“…HIPK2 activity positively correlates with neurodegeneration in ALS (12). Loss of function of HIPK2 has been linked to the development of Alzheimer's disease (13), whereas loss of HIPK3 was implicated as beneficial in Huntington's disease (14).…”
Section: The Homeodomain-interacting Protein Kinase (Hipk) Family Is mentioning
confidence: 99%
“…Loss of Hipk3 results in decreased insulin secretion and impaired glucose tolerance, potentially driving type 2 diabetes (21). Hipk3 Ϫ/Ϫ mice also display lower levels of mutant huntingtin protein, making HIPK3 a potential therapeutic target in Huntington disease (14). Hipk4 knockdown studies identified HIPK4 as a key regulator of human skin epithelial cell differentiation (22).…”
Section: The Homeodomain-interacting Protein Kinase (Hipk) Family Is mentioning
confidence: 99%
“…In addition, the HD knock-in mice also expressed full-length mHtt (Zhao et al, 2016). Emerging evidence has shown that the mHtt aggregates induce cytotoxicity, which is closely related to neuronal death in HD (Lu and Palacino, 2013;Xi et al, 2016), and the reduction in mHtt aggregates has been proven to rescue HD-related phenotypes through genetic and chemical modifications (Jimenez-Sanchez et al, 2015;Yu et al, 2017). Therefore, the clearance of mHtt has become a promising strategy for HD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy plays an important role in maintaining cellular homeostasis by degrading damaged or unnecessary materials in cells (Mizushima and Komatsu, 2011;Gitler et al, 2017;Yu et al, 2017;Pandey and Rajamma, 2018). Intracytoplasmic aggregateprone proteins such as b-amyloid (Ab), hyperphosphorylated tau, mutant a-synuclein and huntingtin rapidly accumulate as autophagy is impaired in cellular and animal models (Kampmann, 2017;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although these previous reports have successfully identified a diverse set of pharmacologically targetable molecules capable of reducing mHTT aggregation and its associated toxicity in cellular and animal models of HD, these target pathways may not directly apply to the endogenous expression of pathological mHTT, especially in the context of HDrelevant human cell types. In a paper recently published in Cell Research [10], Yu et al have expanded upon previous RNAi screens for HD by examining the effects of siRNA knockdown of regulome genes with a rigorous, multiple-step, multiple-platform pipeline to identify candidate genes whose reduction can mitigate two key phenotypes central to HD pathologyelevated levels of mHTT and neuronal toxicity. Importantly, this study is the first of its kind to conduct its primary screening in human cells endogenously expressing mHTT, HD patient-derived fibroblasts, which more accurately recapitulate the mutant protein expression seen in HD patients compared to previously utilized transgenic overexpression models.…”
Section: In a Paper Recently Published Inmentioning
confidence: 99%